Effects of the supplementation of olive cake and cactus pad silage on sheep intramuscular fatty acid composition - Vasta V.; Abidi S.; Ben Salem H.; Nefzaoui A.; Priolo A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
Twelve Barbarine lambs were fed barley and soybean meal concentrate: six lambs were also supplemented with oat hay (H group), while the other six animals were supplemented with silage based on olive cake and cactus pads (S group). Lambs were slaughtered after 92 days of treatment at the age of 242 days. Intramuscular fatty acid composition was determined on m. longissimus dorsi. Meat of the animals supplemented with the silage contained higher levels of C18:2n-6 (P<0.05) and lower C18:3n-3 (P<0.01) compared to the meat from the lambs supplemented with hay. Saturated fatty acids (SFA) were present at higher levels (P<0.05) in the meat of animals of the H group compared to meat from the animals of the S group. The n-6/n-3 ratio was higher (P<0.000) in the fat of the sheep fed the silage diet compared to meat of the animals fed the hay diet.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)